Pengaruh Penyuluhan Gizi Terhadap Perubahan Pengetahuan dan Perilaku Ibu Dalam Pemberian MP-ASI - Ade Ade (Jurnal Ilmu Gizi Indonesia (JIGZI), 2020)
AbstractThe appropriate and good use of breast feeding and the provision of complementary food are the key to maintaining infant nutrition until the age of 24 months. Because the rate of growth and development at the age of under 2 years will determine the process of growth and development of children of later ages. Counseling with demonstration and behavior methods provides better benefits to changes in knowledge and behavior than just counseling. This study aimed to observe the effect of nutrition counseling on changes in maternal knowledge and behavior in the provision of complementary feeding to children 6-24 months. The sample for this research is 32 respondents who will be given nutrition counseling treatment with lecture and demonstration methods using slide media and teaching aids examples of ingredients and prepared food. Paired sample t-test analysis was used to determine the significance of changes in knowledge about complementary food before and after treatment at a 95% confidence level. This study shows that there is an effect of nutrition counseling on changes in the level of knowledge of mothers in the provision of supplementary breastfeeding for children 6-24 months and there is an effect of nutritional counseling on changes in maternal behavior in the provision of complementary feeding for children 6-24 months. Keywords : complementary food, mother’s knowledge, mother’s behavior AbstrakPemanfaatan ASI dan pemberian MP-ASI yang tepat dan baik merupakan kunci pemeliharaan gizi bayi sampai usia 24 bulan. Karena laju tumbuh kembang pada usia di bawah  2 tahun akan  menentukan proses tumbuh kembang anak usia selanjutnya. Penyuluhan dengan metode demonstrasi dan perilaku memberikan manfaat yang lebih baik  terhadap perubahan pengetahuan dan perilaku dibanding hanya dengan penyuluhan saja.  Penelitian ini ditujukan untuk mengobservasi pengaruh penyuluhan gizi terhadap perubahan pengetahuan dan perilaku ibu dalam pemberian MP-ASI pada anak 6-24 bulan. Sampel untuk penelitian adalah 32 responden yang akan diberi perlakuan penyuluhan gizi dengan metode ceramah dan demonstrasi menggunakan media slide dan alat peraga contoh bahan dan makanan jadi. Analisis dengan paired sample t-test digunakan untuk mengetahui kemaknaan perubahan pengetahuan tentang MP-ASI sebelum dan sesudah dilakukan perlakuan pada tingkat kepercayaan 95%. Penelitian ini menunjukkan bahwa terdapat pengaruh penyuluhan gizi terhadap perubahan tingkat pengetahuan ibu dalam pemberian Makanan Pendamping ASI anak 6 - 24 bulan dan terdapat pengaruh penyuluhan gizi terhadap perubahan prilaku ibu dalam pemberian Makanan Pendamping ASI anak 6 - 24 bulan. Kata Kunci : MP ASI, pengetahuan ibu, perilaku ibu